TRANSDISCIPLINARIDADE: UMA ABORDAGEM DA EDUCAÇÃO AMBIENTAL COMO INSTRUMENTO DE AMPLIAÇÃO DA CONSCIENTIZAÇÃO AMBIENTAL DOS ALUNOS DO ENSINO FUNDAMENTAL DE ESCOLAS PRIVADAS DE NITERÓI - Miranda, Roberta Matos de (2011)
This study proposes a transdisciplinary approach to environmental education as an instrument of knowledge aggregator and enhancer through an investigative study on the level of environmental awareness of 220 students in eighth and ninth years of elementary school of 6 (six) of the private networks of schools Oceanic Region of Niterói city. Additionally, clarifications were sought and researched school teaching positions on environmental issues and what methods are used to increase the environmental awareness of students. In preparing the study used the methodology of field research, consisting of interviews with educational coordinators, questionnaires to students and teachers. The observation on the premises of schools served as a complement to research about the involvement of schools in relation to environmental awareness of students. After analyzing the data presented in the results, the survey showed an average percentage of 58.8%, corresponding to an index of environmental awareness of the 178 students in eighth and ninth years of basic education of the five (5) private schools in the city of Niteroi. An educational institution has been excluded from the overall assessment of the environmental awareness of students, depending on imposing limits on themselves, making the implementation of standardized research instruments. In the results, the interdisciplinary approach was manifested by the teachers and coordinators, as a method of expanding the environmental awareness of pupils in these schools. However, it was evident that the approach is guided predominantly found in the Multi-disciplinary approach. Given these misconceptions, a policy proposal to transdisciplinary teaching environmental education in schools brings its contribution to overcoming the knowledge barriers and unifying knowledge, so that environmental issues can be contextualized within and across curriculum subjects. This approach not only broadens the students' knowledge and stimulates critical view on building values and principles appropriate to environmental preservation.